Hippocampal Subfield Volumes in Major Depressive Disorder Adolescents with a History of Suicide Attempt. (13th April 2021) - Zhang, Qi; Hong, Su; Cao, Jun; Zhou, Yi; Xu, Xiaoming; Ai, Ming; Kuang, Li
Abstract : Suicidal behavior is a leading cause of death and often commences during adolescence/young adulthood (15~29 years old). The hippocampus, which consists of multiple functionally specialized subfields, may contribute to the pathophysiology of depression and suicidal behavior. We aimed to investigate the differences of hippocampal subfield volume between major depressive disorder (MDD) patients with and without suicide attempts and healthy controls in adolescents and young adults. A total of 40 MDD suicide attempters (MDD+SA), 27 MDD patients without suicide attempt (MDD-SA), and 37 healthy controls (HC) were recruited. High-resolution T1 MRI images were analyzed with the automated hippocampal substructure module in FreeSurfer 6.0. Volume differences among the groups were analyzed by a generalized linear model controlling for intracranial cavity volume (ICV). The relationship between hippocampal subfield volumes and clinical characteristics (HAM-D and SSI scores) was assessed using two-tailed partial correlation controlling for ICV in MDD+SA and MDD-SA. We found that MDD-SA had significantly smaller bilateral hippocampal fissure volume than HC and MDD+SA. No significant correlation was observed between hippocampal subfield volume and clinical characteristics (HAM-D and SSI scores) in MDD+SA and MDD-SA. Adolescent/young adult suicide attempters with MDD suicide attempters have larger bilateral hippocampal fissures than depressed patients without suicide attempts, independently from clinical characteristics. Within the heterogeneous syndrome of major depressive disorder that holds a risk for suicidality for subgroups, hippocampal morphology may help to explain or possibly predict such risk, yet longitudinal and functional studies are needed for understanding the biological mechanisms underlying.